An Enzymolysis-Assisted Agrobacterium tumefaciens-Mediated Transformation Method for the Yeast-Like Cells of Tremella fuciformis. Issue 1 (2nd January 2019) - Wang, Yuanyuan; Xu, Danyun; Sun, Xueyan; Zheng, Lisheng; Chen, Liguo; Ma, Aimin
Abstract: Agrobacterium tumefaciens -mediated transformation (ATMT), as a simple and versatile method, achieves successful transformation in the yeast-like cells (YLCs) of Tremella fuciformis with lower efficiency. Establishment of a more efficient transformation system of YLCs is important for functional genomics research and biotechnological application. In this study, an enzymolysis-assisted ATMT method was developed. The degradation degree of YLCs depends on the concentration and digestion time of Lywallzyme. Lower concentration (≤0.1%) of Lywallzyme was capable of formation of limited wounds on the surface of YLCs and has less influence on their growth. In addition, there is no significant difference of YLCs growth among groups treated with 0.1% Lywallzyme for different time. The binary vector pGEH under the control of T. fuciformis glyceraldehyde-3-phosphate dehydrogenase gene ( gpd ) promoter was utilized to transform the enzymolytic wounded YLCs with different concentrations and digestion time. The results of PCR, Southern blot, quantitative real-time PCR (qRT-PCR) and fluorescence microscopy revealed that the T-DNA was integrated into the YLCs genome, suggesting an efficient enzymolysis-assisted ATMT method of YLCs was established. The highest transformation frequency reached 1200 transformants per 10 6 YLCs by 0.05% (w/v) Lywallzyme digestion for 15 min, and the transformants were genetically stable. Compared with the mechanical wounding methods, enzymolytic wounding is thought to be a tender, safer and more effective method.